Eastward expansion of the Tibetan plateau: Insights from stress drops of the 2021 Ms 6.4 Yangbi, Yunnan and Ms 7.4 Maduo, Qinghai earthquake sequences in China - He, Xi; Zhao, Lian-Feng; Xie, Xiao-Bi; Zhang, Lei; Yao, Zhen-Xing (Frontiers in Earth Science, 2023)
The eastward expansion of the Tibetan Plateau has resulted in extensive seismic activities in the eastern Tibetan Plateau, along with various types of faulting processes across this region. However, the crustal stress status related to these phenomena remains unclear. On 21 May 2021, the Ms 6.4 Yangbi and Ms 7.4 Maduo earthquakes with diverse focal mechanisms occurred consecutively in the Chuandian and Bayan Har blocks in the southern and northern parts of the eastern Tibetan Plateau, providing a distinct opportunity to directly compare the stresses in both flanks of the laterally expanding plateau. In this study, we estimate the stress drops of the Yangbi and Maduo earthquake sequences for all M≥3.0 events from the Lg-wave spectra. Both the path attenuation and site effect are properly removed based on an established broadband Lg-wave attenuation model. Then, the distribution of the stress drops is refined through high-precision earthquake relocation. Quick decays in stress drops were observed after both mainshocks. The Yangbi sequence has a relatively high median stress drop value, with significantly high stress drops for some foreshocks that possibly indicate a cascade triggering mechanism for the nucleation of the mainshock. In comparison, the Maduo sequence is characterized by a higher stress drop for the mainshock and sustained large fluctuation in stress drops for aftershocks. The Maduo aftershocks extend both the eastern and western directions from the mainshock, with relatively low stress drops in the east, suggesting a large amount of energy has been spent to drive the supershear rupture during the mainshock. We also find that the stress drops are associated with fault junctions for the Yangbi sequence, and are associated with variations in strength along the fault for the Maduo sequence, which are very likely linked with patterns of crustal motion and deformation in the eastern Tibetan Plateau.